First aid Q&A for the NBDE part II - Portnof, Jason E. (McGraw-Hill Medical, 2010)
Machine generated contents note: Pharmacology -- Operative Dentistry and Prosthodontics -- Oral and Maxillofacial Surgery and Pain Control -- Orthodontics -- Pediatric Dentistry -- Endodontics -- Periodontics -- Radiology -- Pathology -- Patient Management, Public Health, Ethics and Biostatistics.